Burning the Candle at Both Ends: Extramarital Sex as a Precursor of Marital Disruption. (November 2013) - DeMaris, Alfred
This study examines several aspects of the association between engaging in extramarital sex and the disruption of one's marriage. Panel data on 1, 621 respondents followed from 1980 to 2000 in the Marital Instability Over the Life Course survey were used to answer these questions. Interval-censored Cox regression analysis revealed several noteworthy findings. As previously found in earlier analyses with these data, reports of problems due to extramarital involvement were strongly related to marital disruption, even holding constant the quality of the marriage. Although men were about three times more likely to be the cheating spouse, there was no difference in the effect of an affair on the marriage according to gender of the cheater. Approximately 40% of the effect of extramarital sex on disruption was accounted for by the mediating factors of marital quality, tolerance of divorce, and wife's employment. Two moderators of infidelity's positive effect on disruption were found: The effect was substantially stronger for very religious couples but weaker when the wife was in the labor force.